Answer:
it's option A .............
I^22 = i^(20 + 2) = i^20 x i^2 = (i^4)^(5) x (i)^2 = 1 x -1 = -1
Answer:
Step-by-step explanation:
So, u would start by expanding the bracket and ignoring the 2 at the moment.
(x+9)(x+9)= x^2-18x+81(using the foil method!
Then u would put 2 at the front to get:
2(x^2+18x+81)
= 2x^2+36x+162
Find the greatest common factor (GCF)
in this case it would be 9
divide each term by the GCF
36 / 9 = 4
9y / 9 = y
put the two "new" terms in parenthesis and the GCF in front of it
9 (4 + y)
it could also be 9 (y + 4) because of Commutative Property of Addition